3D printability of highly ductile poly(ethylene glycol‐co‐cyclohexane‐1, 4‐dimethanol terephthalate)‐EMAA blends. Issue 6 (5th April 2021) - Silva, Philipe A. P.; da Silva, Aline Bruna; Erbetta, Cynthia D'. Avila Carvalho; Santos, João Paulo Ferreira; de Sousa, Ricardo Geraldo; Oréfice, Rodrigo Lambert
Abstract: In this work, ionomers were employed to improve the adhesion between 3D printed layers of poly(ethylene glycol‐co‐cyclohexane‐1, 4‐dimethanol terephthalate) (PETG), a commonly used polymer in 3D printing. The printability, rheology, and mechanical properties of PETG were tailored by incorporating poly(ethylene‐co‐methacrylic acid) neutralized with sodium (EMAA), a soft ionomer. PETG/EMAA polymer blends were prepared by melt extrusion to yield filaments for 3D fused filament fabrication (FFF) printing in different compositions by weight: 70/30, 50/50, and 30/70. The filaments and 3D printed samples were characterized by scanning electron microscopy, rheological and tensile tests. The results revealed that the interaction between PETG and EMAA favored the production of 3D printed samples with enhanced adhesion of layers, ductility, and toughness compared to neat PETG. Increases of 83.5 times in toughness and 86.4 times in ductility were achieved. The blends 30/70 and 50/50 presented the best printability in terms of adhesion between printed layers and mechanical properties. Abstract :